2017
DOI: 10.1016/j.jid.2016.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Polyomavirus-Negative Merkel Cell Carcinoma: A More Aggressive Subtype Based on Analysis of 282 Cases Using Multimodal Tumor Virus Detection

Abstract: Previous studies have reached conflicting conclusions regarding the proportion of Merkel cell carcinomas (MCCs) that contain the Merkel cell polyomavirus (MCPyV) and the clinical significance of tumor viral status. To address these controversies, we detected MCPyV large T antigen using immunohistochemistry with two distinct antibodies and MCPyV DNA using quantitative PCR. Tumors were called MCPyV-positive if two or more of these three assays indicated presence of this virus. A total of 53 of 282 (19%) MCC tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
187
3
19

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 220 publications
(225 citation statements)
references
References 27 publications
16
187
3
19
Order By: Relevance
“…Most studies investigating the prevalence of MCPyV in MCC have used the polymerase chain reaction technique to detect viral sequences, although routine use of this technique is beyond the scope of most standard surgical pathology laboratories. In contrast, immunohistochemical detection of MCPyV using the commercially available CM2B4 antibody can be performed easily in most pathology laboratories . Since the initial reports describing the prevalence of MCPyV, several independent research groups have indicated that the prevalence of MCPyV among MCC cases is approximately 75%, based on values ranging from 24% in Australia to 100% in Europe and Korea, with a wide range of viral load values .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies investigating the prevalence of MCPyV in MCC have used the polymerase chain reaction technique to detect viral sequences, although routine use of this technique is beyond the scope of most standard surgical pathology laboratories. In contrast, immunohistochemical detection of MCPyV using the commercially available CM2B4 antibody can be performed easily in most pathology laboratories . Since the initial reports describing the prevalence of MCPyV, several independent research groups have indicated that the prevalence of MCPyV among MCC cases is approximately 75%, based on values ranging from 24% in Australia to 100% in Europe and Korea, with a wide range of viral load values .…”
Section: Discussionmentioning
confidence: 99%
“…A later study of 60 MCC patients revealed that virus‐negative status was univariately associated with poor overall and recurrence‐free survival rates, although these associations disappeared when tumor stage and nodal involvement were incorporated into the analysis . The largest published study to date (282 MCC patients) has also indicated that MCPyV‐negative MCC is associated with significantly increased risks of MCC progression and related death . However, patients’ viral status does not seem to alter their clinical management, as targeted immunotherapy (programmed cell death protein 1 inhibitor) provides a response in 44% of MCPyV‐negative patients and 62% of MCPyV‐positive patients …”
Section: Discussionmentioning
confidence: 99%
“…In addition, the differing genetic drivers and mutational profiles of MCPyVpositive and MCPyV-negative MCC may have translational significance for prognosis and therapeutics, suggesting further rationale for characterization of MCPyV status (4-6). Although reports on prognostic significance have been mixed regarding whether the presence of MCPyV detection is associated with improved outcome, a recent large prospective study of 282 cases using multimodal MCPyV detection with qPCR and IHC demonstrated significantly better outcome for MCPyV-positive tumors (28). In addition, the presence of MCPyV may influence tumor sensitivity to immunotherapy and targeted therapy (5,29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Histological characteristics of prognostic significance include tumor thickness and the presence or absence of tumor‐infiltrating lymphocytes, especially CD8 + T cells . The prognostic significance of the histological subtype (trabecular, small‐cell, intermediate) and the molecular or immunohistochemical detection of the Merkel cell polyomavirus continues to be the subject of controversial debate . However, more recent studies seem to indicate that tumors not associated with the Merkel cell polyomavirus have a worse prognosis .…”
Section: Introductionmentioning
confidence: 99%